DEVELOPMENT AND IMPROVEMENT OF TECHNOLOGY TO REDUCE OVEN LINING CORROSION - Bekchanova Valida Baxram qizi; Karimov Boxodir Yusufjonovich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2024)
problems such as reducing corrosion of the lining of electric furnaces, ensuring the degree of corrosion of the furnace lining depending on the temperature of the liquid alloy, and the corrosion of the furnace lining depending on the chemical composition of the alloy being liquefied have been solved.